Dimensions of Reporting on Safety Culture in Pre-Post Partum and Perinatology Treatment Rooms (HEALTH CARE: JURNAL KESEHATAN, 2024)
The implementation of good patient safety in pre-postpartum and perinatology units can ensure the quality of services provided to mothers and children runs well. This quality service is expected to reduce the maternal and child mortality rates that still occur today. Reporting patient safety incidents not only plays an important role in ensuring the quality of services but also serves as the main foundation in the organization's learning process and internal improvement within the hospital. The aim of this study is to understand the reporting dimension in the implementation of a patient safety culture in pre-postpartum and perinatology wards. This study combines a mixed-methods approach with a sequential explanatory design. The quantitative method uses the AHRQ (Agency for Health Research and Quality) questionnaire, while the qualitative method employs in-depth interviews. This study involved 52 nurses working in pre-postpartum and perinatology wards. The results showed a positive response of 17.3% in the reporting dimension of the patient safety culture. Based on the interviews, one of the issues hindering the implementation of the patient safety program is the lack of adequate reporting on patient safety incidents, the absence of a good reporting system, a high blaming culture, lack of management support, very slow or lengthy case reporting, and insufficient financial support. The final results of reporting, analysis, and evaluation are limited to internal analysis and evaluation within the hospital. Recommendations from this study include strengthening the safety culture through patient safety training for all staff and continuous monitoring and evaluation of each patient safety program conducted.